MAZMUR DAN PEMBINAAN INTEGRAL PELAYAN FIRMAN - Berthold Anton Pareira (Litbang STFT Widya Sasana Malang, 2002)
There is a general sad observation that the formation of our priestly students is too intellectual to the detriment of its affective element. The students loose the capacity to perceive the things of beauty. How can this situation be remedied? The author of this article is of the opinion that one of the ways out is the study of the Bible as literature and the use of psalms in the atmosphere of beauty. As poetry of christian worship music, chant, oracle, wisdom, prayer, joyful praise and thanks, silence, dance, play, action and architecture are all main elements that make the psalms and therefore should integrated and manifested in their use. Only by then can the students be imbued by their feelings and emotions and be captivated by their beauty. The psalms are a school of integral formation.